Preparation and characterization of a CO2 activated aerated concrete with magnesium slag as carbonatable binder. (24th October 2022) - Lei, Ming; Deng, Simin; Huang, Kaiyun; Liu, Zhichao; Wang, Fazhou; Hu, Shuguang
Highlights: A novel carbonated aerated concrete integrating the large-scale CO2 utilization and magnesium slag recycling is proposed. The CAAC with various densities exhibits a high and rapid development of compressive strength and carbonation degree during the carbonation. The addition of porous zeolite has a certain positive effect on the carbonation degree. Abstract: Magnesium slag is an industrial by-product from magnesium production. Most of magnesium slag is disposed at landfills without being effectively recycled, posing a severe pollution to the environment. Here, a CO2 activated aerated concrete (CAAC) with magnesium slag as the main carbonated binder is reported. Mechanical strength, microstructure, volume stability and CO2 absorption efficiency of CAAC are investigated. Results show that the compressive strengths of CAAC after being carbonated for 2 h with varying densities (400, 600, 800 kg/m 3 ) can reach 2.83, 4.51, and 6.96 MPa respectively. This is associated with the high carbonation reactivity of magnesium slag and the addition of microporous zeolite, which promotes the CO2 diffusion and synchronously increases the degree of carbonation from 45.2 % to 55.1 % in the case of 600 kg/m 3 mix. The high carbonation degree also leads to the absorbed CO2 up to 28 wt%, and more than 90 % of the total CO2 absorption efficiency can be achieved within the first 30 min. In addition, CAAC exhibits high volume stability by the consumption of f-MgO and f-CaO during carbonation. This study provides a new insight into preparation of carbonated aerated concrete integrating the large-scale CO2 utilization and magnesium slag recycling.